2007
DOI: 10.1242/jcs.007310
|View full text |Cite
|
Sign up to set email alerts
|

Rip11 is a Rab11- and AS160-RabGAP-binding protein required for insulin-stimulated glucose uptake in adipocytes

Abstract: The translocation of GLUT4 to the plasma membrane underlies the ability of insulin to stimulate glucose uptake, an event that involves the activation of protein kinase B, several members of the Rab family of GTP-binding proteins and the phosphorylation of the Rab GTPase-activating protein AS160. Here, we explored the regulation by insulin of the class I Rab11-interacting proteins Rip11, RCP and FIP2. We show that Rip11, but not RCP or FIP2, translocates to the plasma membrane of 3T3-L1 adipocytes in response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 53 publications
2
38
0
Order By: Relevance
“…Moreover, the identity of the specific Rab11 effector(s), be they members of the FIPs, Rabphilin-11/RabllBP, myosin Vb, phosphoinositide 4-kinase ␤, or Sec15 (6, 56 -60), that direct the trafficking of the hIP after Rab11 activation remains to be investigated. Given the exquisite relationship that exists between certain Rab11 members and their effectors, as exemplified by Rab25 and Rab-coupling protein in coordinating the agonist-dependent recycling of the ␣5␤1 integrin (54), or Rip11 in regulating insulin-dependent GLUT 4 transport in adipocytes (61), the identification of the Rab11 effector(s) involved in the trafficking of the hIP is likely to add significantly to the understanding of the true physiologic significance of the direct interaction between the hIP and Rab11.…”
Section: C308sc309sc311smentioning
confidence: 99%
“…Moreover, the identity of the specific Rab11 effector(s), be they members of the FIPs, Rabphilin-11/RabllBP, myosin Vb, phosphoinositide 4-kinase ␤, or Sec15 (6, 56 -60), that direct the trafficking of the hIP after Rab11 activation remains to be investigated. Given the exquisite relationship that exists between certain Rab11 members and their effectors, as exemplified by Rab25 and Rab-coupling protein in coordinating the agonist-dependent recycling of the ␣5␤1 integrin (54), or Rip11 in regulating insulin-dependent GLUT 4 transport in adipocytes (61), the identification of the Rab11 effector(s) involved in the trafficking of the hIP is likely to add significantly to the understanding of the true physiologic significance of the direct interaction between the hIP and Rab11.…”
Section: C308sc309sc311smentioning
confidence: 99%
“…it was reported that as160 showed gTPase-activating protein (gaP) activity toward rabs 2a, 8a, 10, 11 or 14. current evidence suggests that akt phosphorylation of as160 suppresses its gaP activity, and consequently increases the gTP-bound rabs and triggers an increase in the rate of gLuT4 vesicle exocytois [15][16][17][18][19]. moreover, as160 was shown to promote the retention of gLuT4 vesicles in intracellular components in 3T3L1 adipocytes [15,20].…”
Section: Materials and Antibodiesmentioning
confidence: 86%
“…Under steady state conditions, NPC1L1 is located predominantly in transferrin-rich recycling vesicles in the perinuclear region (27,28). Absorption of cholesterol requires translocation of NPC1L1 to the cell membrane, a process mediated by a protein complex containing Rab-GTPase-11 (Rab11) and its partner Rab11 family of interacting protein-2 (FIP2) (30,31) or other Rab11-interacting proteins (RIPs), such as Rip11 and Rab-coupling protein (32). The data from this report document the regulatory role of Rab11a in CCK-induced NPC1L1 translocation and cholesterol absorption.…”
Section: Discussionmentioning
confidence: 99%
“…The Akt-phosphorylated GAPs dissociate with the Rab11-RIP protein complex. This dissociation enables the GTP-bound form of Rab11 to drive the recycling vesicle translocation to the cell membrane (32). Insulin also has been shown to induce NPC1L1 translocation from recycling vesicles to the cell surface (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation